Analisis Gangguan Depresi pada Generasi Alfa di Indonesia dan Strategi Pencegahannya: Tinjauan Literatur - Fikki Prasetya; Rahma Fanti; Yuli Solihati; Annisa Qoriyah; Sitti Marzuqoh Aidah Basri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Generation Alpha refers to children born after 2010, who are growing up in a rapidly evolving digital ecosystem. In the Indonesian context, the emergence of depressive disorders among this generation poses a critical mental health challenge that has not been thoroughly addressed. This study aims to analyze the prevalence of depressive symptoms in Generation Alpha, identify the major risk factors, and evaluate current and potential preventive strategies through a narrative literature review approach. Data were collected from national and international journals using platforms such as PubMed, Google Scholar, and Garuda, with inclusion criteria covering articles published between 2019 and 2024 and relevant to children’s mental health. Findings reveal a significant increase in depressive symptoms among children aged 5 to 13 years. Key risk factors include non-democratic parenting styles, academic stress, bullying in school environments, and excessive use of digital gadgets. Additionally, the COVID-19 pandemic and remote learning have exacerbated children’s mental health, particularly among those from low-income families or with limited access to psychological support. On the other hand, preventive strategies involving holistic approaches such as school-based mental health education, play therapy, digital mental health interventions, and Islamic spirituality-based approaches have demonstrated considerable potential in mitigating depressive symptoms. This review highlights the urgency of implementing multi-level and context-sensitive prevention strategies through collaboration between schools, families, and community-based institutions.